Pendidikan sebagai Agen Rekontruksi Budaya - Djamal, M. (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2010)
Abstract : Education can work as an effort to preserve the cultural value system to the children of the nation. This condition was by done by the Old Oder and News Order in order to transform the ideology. Education tries to transform knowledge in the area of reconstruction, especially the reconstruction of culture to position a new value system. With the change in the framework of human thought, the concept of culture itself will shift. Here, the importance of education as a system of meaning that is not binding (the process of liberation), humanizing, and caviling process. This will be done properly if there is critical thinking about methodology, social structure, the rules so that no further transformation. Keywords : Education, Reconstruction, Culture, and Transformation.